Modelling and kink correction of 0.18μm bulk CMOS at liquid helium temperature. Issue 14 (1st July 2019) - Li, Zhen; Luo, Chao; Lu, Tengteng; Xu, Jun; Kong, Weicheng; Guo, Guoping
Abstract : Cryogenic characterisation and modelling of 0.18 μ m CMOS technology (1.8 and 5 V) is presented in this Letter. Several P‐type MOS and N‐type MOS transistors with different width to length ratios were extensively characterised under various bias conditions at temperatures ranging from 300 K down to 4.2 K. The authors extracted their fundamental physical parameters and developed a compact model based on BSIM3V3. A simple subcircuit was built to correct the kink effect. The RMS error of test results and modelling results is < 3%.